Developing STEM-Integrated Interactive Multimedia to Improve Students' Data Literacy and Technology Literacy - Serli Ahzari; Asrizal Asrizal (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Facing industry 4.0 literacy requires a role of literacy. One of the literacies that are suitable for answering the challenges of this era is data and technology literacy. The STEM approach is the learning approach used to address the challenges of the Industry 4.0 revolution. However, the actual conditions in the field describing the application of interactive multimedia by integrating STEM and integrating data and technology literacy in learning still need to be improved. The solution is to develop interactive multimedia by integrating STEM. This research aims to produce valid and practical interactive multimedia by integrating STEM to improve the data and technology of students. The Research & Development stage was completed until limited product testing. The data in this research was obtained from experts' validity and practical results from the students of class 11 science. The data collection instrument consisted of the validity sheet given to the experts and the practicality sheet given to the students of class 11 science. The analysis results show that the STEM-integrated interactive multimedia produced is valid and practical according to students. The second value is included in the very good category. Experts rationally state that interactive multimedia integrating STEM is valid regarding material substance, visual communication display, learning design, software usage, and assessment of STEM components. Students stated that the interactive multimedia presentation integrating STEM was practical regarding usability, ease of use, attractiveness, and clarity.